Invariant manifolds and alternative approaches to reductive perturbation theory: dissipative systems - Hedley C. Morris; Derek Sheil; Roger Dodd (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with the limiting process known as Reductive Perturbation Theory. A new view of both conventional reductive perturbation theory and the higher order theory of Kodama is presented for a general class of dissipative systems. An alternative Iterative approach to the determination of higher order corrections is outlined.